Evaluation Model and Approximate Solution to Inconsistent Max-Min Fuzzy Relation Inequalities in P2P File Sharing System - Xiao-Peng Yang (Complexity)
Considering the requirement of biggest download speed of the terminals, a BitTorrent-like Peer-to-Peer (P2P) file sharing system can be reduced into a system of max-min fuzzy relation inequalities. In this paper we establish an evaluation model by the satisfaction degree, for comparing two arbitrary potential solutions of such system. Besides, based on the evaluation model, concept of approximate solution is defined. It is indeed a potential solution with highest satisfaction degree. Furthermore, effective algorithm is developed for obtaining the approximate solutions to inconsistent system. Numerical examples are provided to illustrate our proposed model and algorithm.